EFFECT OF BABY MASSAGE AND KANGAROO MOTHER CARE TO WEIGHT GAIN ON LOW BIRTH WEIGHT (LBW) - Arief, Windhy Lathifah; Rita, Rauza Sukma; Oktova, Rafika (Indonesian Journal of Health Science, 2024)
Babies with low birth weight (LBW) require more complex treatments. Baby massage and kangaroo method treatment are additional treatments that can be given so that babies experience weight gain. Weight gain is an indicator of growth in babies with LBW. This study aims to determine the effect of infant massage and kangaroo methods on weight gain in LBW babies. Method: Narrative literature review through databases: ScienceDirect, PubMed and Google Scholar using inclusion and exclusion criteria. Results: 20 journals were obtained for analysis. Baby massage carried out by parents for 7 days (3 times a day, for 15 minutes) affected weight gain in low birth weight babies with an average weight gain of 15 grams/day. The kangaroo method, for a minimum of 4-6 hours and carried out directly by the baby's mother, had a more significant effect on weight gain in low birth weight babies with an increase of 6 grams/day. Infant massage interventions and kangaroo methods also had a better effect on weight gain in babies with low birth weight with an average weight gain of 11-23 gr/day. This study concludes that infant massage and kangaroo methods affect weight gain in babies born with LBW.